Neuronal KIF5b deletion induces striatum‐dependent locomotor impairments and defects in membrane presentation of dopamine D2 receptors. Issue 3 (14th February 2019) - Cromberg, Lucas E.; Saez, Trinidad M. M.; Otero, María G.; Tomasella, Eugenia; Alloatti, Matías; Damianich, Ana; Pozo Devoto, Victorio; Ferrario, Juan; Gelman, Diego; Rubinstein, Marcelo; Falzone, Tomás L.
Abstract: The process of locomotion is controlled by fine‐tuned dopaminergic neurons in the Substantia Nigra pars‐compacta ( SNpc ) that projects their axons to the dorsal striatum regulating cortical innervations of medium spiny neurons. Dysfunction in dopaminergic neurotransmission within the striatum leads to movement impairments, gaiting defects, and hypo‐locomotion. Due to their high polarity and extreme axonal arborization, neurons depend on molecular motor proteins and microtubule‐based transport for their normal function. Transport defects have been associated with neurodegeneration since axonopathies, axonal clogging, microtubule destabilization, and lower motor proteins levels were described in the brain of patients with Parkinson's Disease and other neurodegenerative disorders. However, the contribution of specific motor proteins to the regulation of the nigrostriatal network remains unclear. Here, we generated different conditional knockout mice for the kinesin heavy chain 5B subunit (Kif5b) of Kinesin‐1 to unravel its contribution to locomotion. Interestingly, mice with neuronal Kif5b deletion showed hypo‐locomotion, movement initiation deficits, and coordination impairments. High pressure liquid chromatography determined that dopamine (DA) metabolism is impaired in neuronal Kif5b ‐KO, while no dopaminergic cell loss was observed. However, the deletion of Kif5b only in dopaminergic neurons is not sufficient to induce locomotor defects. Noteworthy, pharmacological stimulation of DA release together with agonist or antagonist of DA receptors revealed selective D2‐dependent movement initiation defects in neuronal Kif5b ‐KO. Finally, subcellular fractionation from striatum showed that Kif5b deletion reduced the amount of dopamine D2 receptor in synaptic plasma membranes. Together, these results revealed an important role for Kif5b in the modulation of the striatal network that is relevant to the overall locomotor response. Open science badges: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : Intracellular transport is key for the normal function of neurons that control locomotor outputs. In this issue We show that conditional deletion of the molecular motor Kif5b from neurons leads to axonal transport defects, impaired dopamine metabolism, and reduced membrane D2R levels in the striatum ; resulting in impaired movement initiation, hypo‐locomotion, and motor coordination defects. Open Science: This manuscript was awarded with the Open Materials Badge For more information see:https://cos.io/our-services/open-science-badges/